Sperm chromatin structure assay results in Nigerian men with unexplained infertility - Faduola, Paul (Clin Exp Reprod Med, 2015)
OBJECTIVE: Several publications have established a relationship between sperm DNA damage and male factor infertility, based on data from America, Europe, and Asia. This study aimed to compare the extent of sperm DNA damage in sperm samples from Nigerian men with unexplained infertility and in sperm samples from a fertile group composed of sperm donors who had successfully impregnated a female partner naturally or through assisted conception. METHODS: A total of 404 men underwent male fertility evaluation at Androcare Laboratories and Cryobank participated in this study. Semen analysis and a sperm chromatin structure assay (SCSA) were performed on all subjects. RESULTS: The men in the unexplained infertility group were slightly older than the men in the fertile sperm group (36±10 years vs. 32±6 years, p=0.051). No significant difference was observed between the two groups in semen analysis parameters (p≥0.05). Men in the unexplained infertility group with normal semen parameters had a significantly higher DNA fragmentation index (DFI) than men in the fertile sperm group (27.5%±7.0% vs. 14.1%±5.3%, p<0.05). In the unexplained infertility group, 63% of the men had a DFI greater than 20%, compared to 4% in the fertile sperm group. In the unexplained infertility group, 15.2% of the subjects had a DFI greater than 30%, compared to 1% in the fertile sperm group. CONCLUSION: Our study showed that the SCSA may be a more reliable predictor of fertility potential than traditional semen analysis in cases of unexplained infertility.